MENTORING EVALUATION OF PESANTREN EDUCATION IN IMPROVING THE QUALITY OF LEARNING PROGRAMS INTEGRATED - Subasman, Iman; Sukarnoto, Toto; Firmansyah, Bambang (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Community service aims to assist the implementation of educational evaluation in pesantren as an effort to improve the quality of integrated learning programs. Pesantren as educational institutions that organize academic, religious, and character building learning require a reflective and sustainable evaluation system. Service activities are carried out with a Participatory Action Research (PAR) approach that places pesantren managers and educators as active participants in all stages of assistance. The service process is carried out in stages through identification of program conditions, implementation of educational evaluation, joint reflection, and formulation of recommendations for improvement. The results of the assistance show that the foreign language program, tahfidz Al-Qur'an, academics, and character building through halaqoh tarbawiyah already have positive and sustainable learning practices. Evaluative assistance helps strengthen these practices through collaborative alignment of program objectives, processes and evaluation. Educational evaluation is understood not as an instrument of control, but as a means of institutional learning and strengthening a culture of quality. This service contributes to the development of humanist, participatory, and contextualized educational evaluation practices in supporting the sustainable improvement of pesantren education quality.